2021
DOI: 10.1108/ijrdm-03-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

Complaint behaviour in multichannel retailing: a cross-stage approach

Abstract: PurposeThis paper analyses how the purchase channel and customer complaint goals affect the sequential choice of post–purchase complaint channels when customers experience a service failure followed by a service recovery failure (double deviation).Design/methodology/approachAn online survey involving a scenario manipulation was conducted with 577 apparel shoppers. The study employs multi-group latent class analysis to estimate latent customer segments within both online and offline groups of shoppers and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This would entail shop format attributes (Reutterer and Teller, 2009) and other retail settings such as online shopping areas. For example, research on customer complaint management indicates that different distribution channels induce varied complaint behaviours (Frasquet et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would entail shop format attributes (Reutterer and Teller, 2009) and other retail settings such as online shopping areas. For example, research on customer complaint management indicates that different distribution channels induce varied complaint behaviours (Frasquet et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This would entail shop format attributes (Reutterer and Teller, 2009) and other retail settings such as online shopping areas. For example, research on customer complaint management indicates that different distribution channels induce varied complaint behaviours (Frasquet et al, 2021). Likewise, future research on UCB could equally look at behavioural differences within various distribution channels and differing contexts (e.g.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Channel switching may also occur due to cost avoidance motives, which appear to lead customers to less personal and less interactive channels such as the internet (Barwitz and Maas 2018 ; Boardman and McCormick 2018 ), notwithstanding the finding by Kukar-Kinney and Close ( 2010 ) that waiting for sale or lower prices is one of the main reasons for online shopping cart abandonment and subsequent purchase in brick-and-mortar stores. For redress-seeking, a need unique to the after-sales stage, Miquel-Romero et al ( 2020 ), Mattila and Wirtz ( 2004 ) and Frasquet et al ( 2021 ) showed that customers tend to visit interactive complaint channels such as brick-and-mortar stores. If dissatisfaction with a product is high, the importance of a channel’s convenience wanes and customers focus more on redress – a scenario that exemplifies the influence of customer needs on the relative significance of perceived channel characteristics.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…This would also explain the frequent choice of physical stores and social media channels for complaints (Dalla Pozza 2014 ; Frasquet et al 2019 ; Miquel-Romero et al 2020 ). Interestingly, when customers choose a complaint channel for a second complaint after an unsatisfactory first attempt, they tend to switch channels again; probably to take advantage of synergy effects between the channels (Frasquet et al 2021 ).…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation